Implementation of Right Skill Targets on the Human Experience Management System Case Study at PT PLN (Persero) - Ferdiaz, Muhammad Raihan (Journal of Economics and Business UBS, 2023)
PT PLN (Persero) consistently encourages transformation and innovation in Human Capital governance. To support the transformation as a whole, it is critical to have a qualified HR system that can support the formation of superior talents who will act as the driving force for transformation. The Role of Human System Management is very important in advancing the company. Human Capital Transformation will be carried out comprehensively and integrated with the technology and value employee experience bases throughout the PLN, and in accordance with the implementation of the HC roadmap in 2022, namely the Human Experience Management System (HXMS). The Purpose of this study is to understand the implementation right skill target on Human Experience Management System at PT PLN (Persero) from distinction between Human Capital System Management and Human Experience Management System, To analyze and evaluate the impact implementation Right Skill on Human Experience Management System and To optimize implementation of right skill target on Human Experience Management System. This research was conducted using qualitative methods. Qualitatives methods as research methods in a natural setting area that allows the researcher to obtain detailed data from actual experience and Data Analysis evaluation using Nvivo. The results of this study will show that Human Experience plays a crucial role as a change enabler in PLN Transformation program because it is recognized as a more valuable asset than the individual. And to optimizing the implementation of Right Skill Target on Human Experience Management System is develop an integrated system that enables businesses to manage various aspects of human resources